The Genetics of Pandan-Like Fragrance, 2-Acetyl-1-Pyrroline, in Crops - Prakit Somta; Kuswanto Kuswanto; Peerasak Srinives (AGRIVITA, Journal of Agricultural Science, 2019)
The main advantages of pandan (Pandanus amaryllifolius (Roxb.) is the fresh leaves which mainly used for the pleasant fragrance in cuisine. 2-acytile-1-pyrroline (2AP) (also known as 1-(3,4-dihydro-2H-pyrrol-5yl)ethanone) is the principle volatile chemical responsible for the fragrance in pandan.  2AP was identified for the first time from the cooked rice. Many cultivars of certain crops also produce pandan-like fragrance/2AP including rice (Oryza sativa L.), sorghum (Sorghum bicolor (L.) Moench), mungbean (Vigna radiata (L.) Wilczek), soybean (Glycine max (L.) Merr.), coconut (Cocos nucifera L.), cucumber (Cucumis sativus L.), wax gourd (Benincasa hispida), and taro (Colocasia esculenta (L.) Schott). The fragrant crop varieties command higher price than non-fragrant cultivars. Breeding for fragrance is a main goal in breeding programs in these crops. Although genetics studies revealed that the presence of fragrance in crops is monogenic trait and that mutation(s) resulting in null or reduced function of betaine aldehyde dehydrogenase 2 (BADH2)/amino aldehyde dehydrogenase (AADH) causes production of 2AP, the level of the fragrance is quantitative in nature. In this paper, we review and discuss the genetic controls of the fragrance in some crops.